2011
DOI: 10.4103/0970-0218.84129
|View full text |Cite
|
Sign up to set email alerts
|

Profile of home-based caregivers of bedridden patients in North India

Abstract: Background:Caregiving to bedridden patients in India is set to become a major problem in future.Objective:To ascertain the profile of caregivers for the adult bedridden patients in Chandigarh, India.Materials and Methods:This cross-sectional study was conducted on 100 purposively selected bedridden people. The Katz Index of the activities of daily living was used to ascertain their degree of disability. Patients and families were interviewed about the patterns of care provision.Results:The mean age of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…The patient's primary caregiver was defined as a close blood relative which includes the individual's parents or their children who are with the patients for most of the time and provide majority of the care to the patients in the hospital as well as home care settings. The burden falls most heavily on spouses, parents, adult children however secondary kins are less affected [10]. In one of the studies on home based caregivers of bedridden patients, 54% of the key caregivers were blood relations of the patients, out of them 29% were children of the patient [11].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's primary caregiver was defined as a close blood relative which includes the individual's parents or their children who are with the patients for most of the time and provide majority of the care to the patients in the hospital as well as home care settings. The burden falls most heavily on spouses, parents, adult children however secondary kins are less affected [10]. In one of the studies on home based caregivers of bedridden patients, 54% of the key caregivers were blood relations of the patients, out of them 29% were children of the patient [11].…”
Section: Discussionmentioning
confidence: 99%
“…Bedridden patients. Are patients who are unable to move out of bed or confined to bed due to old age, physical impairment, mobility problems, illness or injury or arising from medical restriction to ambulate [25].…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Prevention of PUs is an important indicator to be considered while assessing the quality of care provided by any healthcare facility and is more cost-effective than treatment of PUs. [ 6 10 11 ] The interventional studies on prevention of PUs were primarily reported from developed countries and mostly used specialized pressure-relieving devices (PRDs) and nutritional supplementation with or without educational interventions. [ 3 12 13 ] Although these interventions were cost-effective compared to treatment of PUs, the cost incurred to prevent each PU was also high in the context of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative types of healthcare facilities such as long-term care and home care are also not routinely available, and the family caregivers are the primary caregivers of immobile patients in India. [ 11 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation